Comparison between iSpring Suites-supported PBL and PjBL Model in Improving Students Understanding of Electrolyte and Non-Electrolyte Solution - Juniar, Anna; Purba, Hotma Damayanti (Jurnal Pendidikan MIPA, 2023)
This study aimed to determine whether there are significant differences in learning outcomes in the cognitive, affective, and psychomotor aspects of students who are taught with the Problem Based Learning and Project Based Learning models assisted by iSpring media on electrolyte and non-electrolyte solution materials. This research method is a quasi-experiment with a two-class pretest-posttest research design. Sampling was carried out using purposive sampling technique, and class X PMIPA 3 was selected as the experimental class I which was taught using the Problem Based Learning model assisted by iSpring media and X PMIPA 4 as the experimental class II which was taught by the Project Based Learning model assisted by iSpring media. The instruments used were tests in the form of pretest posttest sheets and non-tests in the form of assessment sheets on the affective and psychomotor aspects of students. Based on the results of the study, the average cognitive aspect learning outcomes were 83.71 in the experimental class I and 80.57 in the experimental class II. The average affective learning outcomes were 55.25 in the experimental class I and 55.05 in the experimental class II. The average learning outcomes of the psychomotor aspects were 78.57 in the experimental class I and 75.02 in the experimental class II. Therefore, it can be concluded that there is a significant difference in learning outcomes in the cognitive and psychomotor aspects of the two experimental classes, while in the affective aspect there is no significant difference. Keywords: problem based learning, project based learning, iSpring, chemistry learning outcomes. DOI: http://dx.doi.org/10.23960/jpmipa/v24i2.pp432-441